Summa theologica - Thomas, Aquinas, Saint, 1225?-1274; Dominicans. English Province (1981)
One of the world's most renowned masterpieces, this brilliant synthesis of Christian thought has had a decisive and permanent impact on religion since the thirteenth century and has become substantially the official teaching of the Catholic Church. No library is complete without it.
"The work is easy to consult and convenient to handle. It should be of inestimable value to students of religion in colleges, seminarians, libraries, educators, professionals, clergy, religious, and laity, to all who are interested in core Christian thought" (A. G. Sertillanges, O.P., The Intellectual Life).
"Unequalled in importance by any other theological text. Its resources are inexhaustible" (National Catholic Register).
"No theologian in the entire history of the Church has had such a decisive impact on Catholic thought as St. Thomas Aquinas" (Catholicism).
V. 1. 1aQQ. 1-119, 1aIIaeQQ. 1-4 -- v. 2. 1aIIaeQQ. 1-114 -- v. 3. IIaIIaeQQ. 1-148 -- v. 4. IIaIIaeQQ. 149-189, IIIa QQ. 1-73 -- v. 5. IIIa QQ. 74-90, Supplement QQ. 1-99, chart of the Summa, analytical index.
Reprint. Originally published: New York : Benziger Bros., 1947-1948.
Vol. 5 includes index.
Includes index.
Translation of: Summa theologica.
Keywords: Catholic Church -- Doctrines; Theology, Doctrinal -- Early works to 1800.; Reference works